Interdisciplinary eHealth for the care of people living with traumatic brain injury: A systematic review. (6th December 2017) - Tran, Vivienne; Lam, Mary K.; Amon, Krestina L.; Brunner, Melissa; Hines, Monique; Penman, Merrolee; Lowe, Robyn; Togher, Leanne
ABSTRACT: Objective : To identify literature which discusses the barriers and enablers of eHealth technology and which evaluates its role in facilitating interdisciplinary team work for the care of people with a traumatic brain injury (TBI). Design : Systematic review. Data sources : Studies were identified by searching CINAHL, Embase, Medline, PsycINFO, Scopus, and Web of Science. Study selection : Studies included in the review were required to feature an eHealth intervention which assisted interdisciplinary care for people with TBI. Data extraction : Descriptive data for each study described the eHealth intervention, interdisciplinary team, outcomes, and barriers and facilitators in implementing eHealth interventions. Results : The search resulted in 1389 publications, of which 35 were retrieved and scanned in full. Six studies met all the inclusion criteria for the review. Four different eHealth interventions were identified: (i) an electronic goals systems, (ii) telerehabilitation, (iii) videoconferencing, and (iv) a point-of-care team-based information system. Various barriers and facilitators were identified in the use of eHealth. Conclusion : eHealth interventions have been reported to support interdisciplinary teams for the care of TBI. However, there is a substantial gap in existing literature regarding the barriers and enablers which characterize a successful interdisciplinary eHealth model for people with TBI.